2009
DOI: 10.1007/s11357-009-9106-3
|View full text |Cite
|
Sign up to set email alerts
|

Revealing system-level correlations between aging and calorie restriction using a mouse transcriptome

Abstract: Although systems biology is a perfect framework for investigating system-level declines during aging, only a few reports have focused on a comprehensive understanding of system-level changes in the context of aging systems. The present study aimed to understand the most sensitive biological systems affected during aging and to reveal the systems underlying the crosstalk between aging and the ability of calorie restriction (CR) to effectively slow-down aging. We collected and analyzed 478 aging- and 586 CR-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…Our data revealed that genes associated with immune and stress response were activated with aging, whereas genes associated with lipid metabolism, cellular growth and maintenance, protein synthesis, and cellular communication were downregulated, consistent with other independent studies, such as gene expression in human retina (Yoshida et al 2002), gene expression profiling of aging rat liver (Tollet-Egnell et al 2001), age-associated changes in gene expression in human liver (Thomas et al 2002), and mouse transcriptome (Hong et al 2010; Schumacher et al 2008). The functional pathways were also consistent with previous studies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our data revealed that genes associated with immune and stress response were activated with aging, whereas genes associated with lipid metabolism, cellular growth and maintenance, protein synthesis, and cellular communication were downregulated, consistent with other independent studies, such as gene expression in human retina (Yoshida et al 2002), gene expression profiling of aging rat liver (Tollet-Egnell et al 2001), age-associated changes in gene expression in human liver (Thomas et al 2002), and mouse transcriptome (Hong et al 2010; Schumacher et al 2008). The functional pathways were also consistent with previous studies.…”
Section: Discussionsupporting
confidence: 84%
“…Most recently, Hong et al (2010) gathered genes related to aging and calorie restriction (CR) from numerous published studies and from microarray datasets in the GEO repository. We found that a significant number of our aging genes were in common with our analysis results ( p value <0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, gene expression analysis of CR has been conducted to identify associated genes (Lee et al, 1999(Lee et al, , 2000. A number of molecular signatures have emerged from such studies that could be useful to identify candidate processes and pathways that affect aging, biomarkers (see below), and candidate regulators (Anderson and Weindruch, 2010;Hong et al, 2010).…”
Section: A Functional Genomics Of Aging and Longevitymentioning
confidence: 99%
“…Hong et al [51] applied systemsbiology approaches to analyze and elucidate correlations among genes involved in aging and CR, and revealed the systems underlying the crosstalk between aging and the ability of CR to effectively slow-down aging. The authors collected and analyzed 478 aging-related and 586 CR-related mouse genes and found that the transcriptome for both aging and CR were strongly negatively related in the immune response, lipid metabolism, and cell adhesion functions.…”
Section: Evidence For Molecular Inflammation In the Aging Process As mentioning
confidence: 99%